Determination of priority of the construction of irrigation network (International Journal of Agricultural Research, Innovation and Technology, 2017)
Development of the irrigation network is one of the factors that give the great impact to economic growth in Indonesia. The Indonesian government has the authority on this development. However, the handling of the irrigation network has not been maximum and cannot meet the expectations/needs during this time. This is because the limitation of government funding which is not in a good proportion to the increasing of the damage of the irrigation network from year to year and the priority scale is only based on the proposed community and the desire of some of the stakeholders. Therefore, a research is important to determine priority scale, which is appropriate to the real needs in the field. The method applied in this research was descriptive research by spread over the questioner to the stakeholders related to the development of the irrigation network and analyzed the data using Analytic Hierarchy Process (AHP). The location of the research was in Sidoarjo Regency that covers 10 locations. The analysis results showed the priority order execution of irrigation network development in accordance with the requirements of the irrigation network. It is expected that this method can be applied to the entire development of the irrigation networks and other infrastructures, therefore, limited government funds can be used efficiently and effectively.Int. J. Agril. Res. Innov. & Tech. 6 (2): 61-68, December, 2016